Application of the Octave software in the relevant learning of Calculus I, of university students of Environmental Engineering - Mario Román Flores Roque (2024)
The main purpose of this research was to determine the influence of the application of the Octave software on the relevant learning of Calculus I, of the Environmental Engineering students of the National University of Moquegua in 2021. A quasi-experimental design was used, with a group control group composed of 32 students and another experimental group composed of 23 students where the evolution of calculus learning was analyzed, before and after the application of the Octave software, through the use of a Pre Test and another Post Test. Hypothesis testing was carried out using Student’s T test for related samples and independent samples. The results determine that there is a very significant influence of the application of the Octave software on the relevant learning of calculus I, at 0.001 significance in the Student’s t test, from which it is concluded that the application of the Octave software positively influenced academic performance. of the student and their level of satisfaction is very high.